Demographic analysis of the irruptive dynamics of an introduced sika deer population. Issue 9 (13th September 2018) - Takeshita, Kazutaka; Ueno, Mayumi; Takahashi, Hiroshi; Ikeda, Takashi; Mitsuya, Ryoko; Yoshida, Tsuyoshi; Igota, Hiromasa; Yamamura, Kohji; Yoshizawa, Ryo; Kaji, Koichi
Abstract: Irruptions of large herbivores, with a rapid population increase to peak abundance, are widely observed. Occasionally, there is a population crash following such peaks in abundance, after which the population recovers to form another peak typically lower than the initial. There are mathematical models describing this full cycle of irruptive dynamics. The insight for further improvement of such mathematical models will be obtained from demographic analyses of irruptive dynamics incorporating density‐dependent and density‐independent resource limitations. Using a 35‐yr dataset on the irruptive dynamics of an introduced sika deer ( Cervus nippon ) population on Nakanoshima Island, Japan, we evaluated the factors and stages determining irruptive dynamics (phase 1: the initial irruption and population crash; phase 2: subsequent dynamics) through key‐factor/key‐stage analysis of the population structure, estimated using age‐at‐death data of naturally dead deer. We set two factors (i.e., deer density and snow accumulation) and three life stages (i.e., immature individuals, adult female, and adult male). The estimated population structure showed two population crashes and a density peak higher than the initial peak during population regrowth subsequent to the initial population crash. The most influential factor and stage for determining the population dynamics differed between phases 1 and 2. The contribution of deer density to the variability in population change was the largest in phase 1 (62.30%) and decreased to 24.10% in phase 2. The contribution of snow accumulation was small in both phase 1 (11.74%) and phase 2 (0.64%). The male stage had the largest contribution in phase 1 (39.23%), while the immature stage had the largest contribution in phase 2 (63.31%). The female stage had the smallest contribution in both phase 1 (24.19%) and phase 2 (17.67%). Population growth rate decreased, while carrying capacity increased, in phase 2 compared to phase 1. We suggest that the small contributions of density‐dependent and density‐independent resource limitations on population dynamics in phase 2 were related to the characteristics of alternative foods (fallen leaves and woody plants) that were newly utilized by deer in phase 2. We conclude that alternative resources potentially generate various irruptive dynamics, including unstable dynamics not expected in the classic paradigm.